The Extended q- Image (basic analogue) of Mittag-Leffler Function and itas Simply Properties (Global Journal of Science Frontier Research, 2018)
In the present paper, the authors derived the basic analogue of extended Mittag-Leffler function by using the extended q-beta function and obtain some important results of Mittag-Leffler function in terms of generalized Wright function. Special cases are also discussed at the end section of paper.
Keywords: extended q-beta function; fractional q-operator; basic analogue of the extended mittagleffler function